DIELECTRIC DISPERSIVE BEHAVIOUR OF SILICON MONO OxcnE THIN FILM SAND WICHED STRUCTURE ANNEALED AT DIFFERENT TEMPERA TURES (Biological Sciences - PJSIR, 2003)
Dielectric properties  of evaporated  silicon  mono oxide film sandwiched  between  aluminium electrodes have been  studied   in the frequency range from 0 . 1 Hz to !MHz . The struct ures were prepa red on glass slide by in situ deposition  of aluminium through successive evaporation in vacuum of the order of  10-5  torr.  The structures  were annealed  at tempera tures  of   303 °K to 378  °K  for five minutes  and  the  effect of annealing  is discussed.  Dielectric  paramters  were  measured by alternating current (AC) impedence technique of Frequency Response Analvzer. The capacitance C ' (permitivity), conductance G and the loss  factor g" were  found  to depend  on  freq uency  and temperature,  within  high  frequency  range the  capacitance  varies  very  slowly,  shO\ving  the  dielect ric  dispersive  nature  and  temperature  independ ent  at  high  fre q uencies . The experimental evidence on the freq uency domain behaviour of this structure h ave been discussed . The result s were best analyzed by comparing them ,vith the power law  frequency  dependence curve  which  departs  from Debye like dielecric behaviour. The a.c cond uctance G of such samples varies dircctity to (co") , ol being  the  circular frequency, and n is a number, which  is less than  one and  is a temperature  dependent  quantity.  The  slope of  loss curve is  not symme-trical with the loss peak. It is emphasised that these experimental results  cannot  be  analysed  in  terms  of  quantum hopping cond uction mechanism proposed  by  Johnschere . The  aim of this  investigation  is to  study  the  dielec  tric response in the specific temperature range of deposited  SiO films and  to prepare  initially the low cost  Schottky diodes  and  other  basic  components